Sending Messages to Influence People - Cristina Guarneri (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2022)
Writing is one of the most influential ways to reach a target audience. It is through words that we can send a message of strength. Such writing often will lead to action, both positive and negative. The greatest power of writing is its ability to affect others with words. Written words are stronger and possess great emphasis compared to spoken words. Recognizing the power of the written word also means the importance of including structural parts to writing, such as sentence structure and more importantly, the thesis statement, which allows for the writer to persuade people prone to being skeptical to what they hear and read. Understanding how to include thesis statements, identifying points of view, and credibility writers can share their stories that allow for the power of the written word to prevail.